Breach of fiduciary duty claims and the quiet fiduciary thesis. Issue 2 (22nd January 2019) - Islam, Carl
Abstract: In arriving at the conclusion that a claim for fraudulent calumny can be brought on the grounds of breach of fiduciary duty where a fiduciary has been silent (the 'Quiet fiduciary thesis'), the author examines: the approach of the court to breach of fiduciary duty claims—ie the framework of applicable legal principles; the hallmarks of a fiduciary—ie who is a fiduciary; the scope and content of fiduciary duties—ie the nature of the duties which define a fiduciary; and the equitable remedies available to the claimant which result—ie the remedial consequences of breach of fiduciary duty, which include: (i) the availability of the section 21(1) Limitation Act 1980 carve-out; (ii) equitable proprietary remedies, including tracing in equity, which is not defeated by the irretrievable mixing of property, Agip (Africa) Ltd v Jackson [1991] Ch 417; and (iii) the non-application of common law principles of remoteness in claims for equitable compensation based upon breach of fiduciary duty. (the 'fiduciary principle'). After applying the Fiduciary Principle to demonstrate the validity of the Quiet Fiduciary Thesis, the author discusses the operation of the fiduciary principle in the wider commercial and contractual context. Because rescission is a self-help remedy at common law, in equity the question that arises is, ' can a contract be rescinded on the grounds of breach of fiduciary duty, by reason of silence/non-disclosure e.g. by a company director or co-venturer? ' The author concludes that it can. The principles applicable to breach of fiduciary duty claims in the context of a commercial joint-venture were recently examined in: Glenn v Watson & Ors [2018] EWHC 2016 (Ch) (31 July 2018) and Sheikh Al Nehayan v Kent [2018] EWHC 333 (Comm).